2020
DOI: 10.1038/s41537-020-0099-3
|View full text |Cite
|
Sign up to set email alerts
|

Language in schizophrenia: relation with diagnosis, symptomatology and white matter tracts

Abstract: Language deviations are a core symptom of schizophrenia. With the advances in computational linguistics, language can be easily assessed in exact and reproducible measures. This study investigated how language characteristics relate to schizophrenia diagnosis, symptom, severity and integrity of the white matter language tracts in patients with schizophrenia and healthy controls. Spontaneous speech was recorded and diffusion tensor imaging was performed in 26 schizophrenia patients and 22 controls. We were able… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
51
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 77 publications
(90 reference statements)
9
51
0
Order By: Relevance
“…Information transfer between prefrontal and temporal language-relevant regions is crucial for efficient language production 36,37 . A recent study by our group revealed that integrity of white-matter language pathways is associated with broad language disturbances in schizophrenia 38 . High D2R occupancy drugs may induce a hypodopaminergic stage and reduce information processing in language tracts, and thus give rise to language disturbances related to cognitive fluency or efficiency (i.e.…”
Section: Discussionmentioning
confidence: 91%
“…Information transfer between prefrontal and temporal language-relevant regions is crucial for efficient language production 36,37 . A recent study by our group revealed that integrity of white-matter language pathways is associated with broad language disturbances in schizophrenia 38 . High D2R occupancy drugs may induce a hypodopaminergic stage and reduce information processing in language tracts, and thus give rise to language disturbances related to cognitive fluency or efficiency (i.e.…”
Section: Discussionmentioning
confidence: 91%
“…Several approaches have been reported regarding brain rhythmicity [ 30 ] or category fluency [ 31 ] and genes, network connectivity using a computational model [ 32 ], symptomatology and white matter tracts [ 33 ], and relationship with antipsychotic medication [ 34 ]. Although the reading mechanism of DNA sequence is well-understood biologically, the cognitive mechanism of language remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies deal with the linguistic habits of psychopathologies, e.g. schizophrenia [12][13][14], personality disorder [15], anxiety and depression [16][17][18][19][20][21][22]. However, a very limited number of papers have been devoted to linguistic changes in patients with eating disorders [23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%